Peculiarities of the consumption behaviour on the real estate market in Romania in the context of the Covid-19 Pandemic - MUNTEANU, George Marius; CREȚOIU, Raluca Ionela (Annals of Spiru Haret University. Economic Series, 2021)
For many of the developed or developing national economies, real estate markets are areas of activity capable of substantially contributing to the structural good functionality of that economy. Transactions carried out within real estate markets provide logistical support for the proper conduct of a multitude of production activities or services of economic operators, on various levels of the economy. From this point of view, any large-scale crisis that also affects real estate field is a major challenge for the proper revitalization of many sectors and for the re-entry into a normal phase of most trade within economy. The crisis caused by the COVID-19 pandemic is a very special crisis not only because of the world scale and large span, but also because of the many plans on which it acted, economically, socially, politically, biologically, etc. This article aims to delve into the picture of the evolution of the Romanian real estate market during the pandemic, providing the main coordinates of this development and assessments on the implications that these market trends have at both Romanian and European market levels.